Separate coronary arteries originating from the right sinus of Valsalva - Küçükdurmaz, Zekeriya; Sezen, Yusuf; Karapinar, Hekim; Gül, İbrahim; Yilmaz, Ahmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Three separate coronary arteries originating from the right or left coronary sinus of Valsalva are exceedingly rarely seen coronary anomalies. The clinical course depends on the site of origin and the anatomical trace. We report a case with all coronary arteries arising from the right sinus of Valsalva with different ostia.